Persepsi Konsumen Terhadap Promosi Pada Aplikasi “FISDOK” Solusi Smart Pelayanan Kesehatan: Study kasus: Desa Banjarsari, Kecamatan Gajah, Kabupaten Demak - Yane Puspito Sari (MAMEN: Jurnal Manajemen, 2022)
Promotion is one of the factors that influence purchasing decisions. Promotion is an important factor that must be done by a company. With promotion, a company can provide information to consumers about the products it creates. The advantages of these products can be known by consumers through promotions and can generate interest in consumers to buy these products. Promotion is a communication activity carried out by a company to explain to consumers about the products created by the company. Promotion is a variety of ways to inform, persuade, and remind consumers directly or indirectly about a product or brand being sold. The problems discussed are limited to consumer perceptions of promotions in the "FISDOK" application, a smart solution for health services. The purpose of this research is to find out how the people of Banjarsari Village, Gajah Subdistrict, Demak Regency recognize the "FISDOK" application and what obstacles are faced in the process of promoting the "FISDOK" application. Data collection techniques and data analysis were obtained from observations, interviews, documentation and, library. The result of the research is that the people of Banjarsari were not familiar with the FISDOK application until the promotion was carried out by the author and the team. On average, people who use the FISDOK application say that this application is very helpful for the community to find out their health condition by consulting directly through the application. With the results of this promotion, the public finally knows and learns about the features contained in this health application. The educational videos contained in the application also greatly provide additional knowledge to the public about physiotherapy.